Integrin-Ligand Interactions in Inflammation, Cancer, and Metabolic Disease: Insights Into the Multifaceted Roles of an Emerging Ligand Irisin - Park, Eun Jeong; Myint, Phyoe Kyawe; Ito, Atsushi; Appiah, Michael G.; Darkwah, Samuel; Kawamoto, Eiji; Shimaoka, Motomu (Frontiers in Cell and Developmental Biology, 2020)
Integrins are transmembrane proteins that mediate cellular adhesion and migration to neighboring cells or the extracellular matrix, which is essential for cells to undertake diverse physiological and pathological pathways. For integrin activation and ligand binding, bidirectional signaling across the cell membrane is needed. Integrins aberrantly activated under pathologic conditions facilitate cellular infiltration into tissues, thereby causing inflammatory or tumorigenic progressions. Thus, integrins have emerged to the forefront as promising targets for developing therapeutics to treat autoimmune and cancer diseases. In contrast, it remains a fact that integrin-ligand interactions are beneficial for improving the health status of different tissues. Among these ligands, irisin, a myokine produced mainly by skeletal muscles in an exercise-dependent manner, has been shown to bind to integrin V5, alleviating symptoms under unfavorable conditions. These findings may provide insights into some of the underlying mechanisms by which exercise improves quality of life. This review will discuss the current understanding of integrin-ligand interactions in both health and disease. Likewise, we not only explain how diverse ligands play different roles in mediating cellular functions under both conditions via their interactions with integrins, but also specifically highlight the potential roles of the emerging ligand irisin in inflammation, cancer, and metabolic disease.